Multiple New or Updated Satellite Total Solar Irradiance (TSI) Composites (1978–2023) - Connolly, Ronan (2024)
Several total solar irradiance (TSI) satellite missions have been carried out since 1978. None of these missions have lasted more than one to two solar cycles (SCs), and each mission implies a slightly different absolute TSI baseline. Nonetheless, several satellite composites have been developed by compositing satellite data from different missions to form an almost continuous daily record for the satellite era. However, disconcertingly, each mission has implied slightly different changes in TSI between consecutive solar minima and solar maxima. Some groups have developed adjustments to individual missions that have substantially reduced these differences. Others prefer to use the original data published by the satellite science teams. Some TSI composites average together conflicting records, while others prioritize specific records over others. Here, we compare four existing composites to 17 new alternative series based on the available satellite data. These 21 TSI series are statistically sorted into six groups of three to four series each. We found that the six groups suggest different intercycle trends between solar minima. We compare the groups to eight daily resolved solar proxy-based TSI reconstructions and to daily sunspot numbers. Excellent agreement is obtained over one to two SCs, but significant differences are observed over longer timescales for each group. Therefore, we have assembled all these time series (old and new) into a large and new TSI data set for use by the scientific community. Versions scaled to 1 au (for studying solar variability) or in situ values at Earth (for studying solar/terrestrial interactions) are provided at daily, monthly, and yearly resolutions.